Teenswoordige heil, verbond en sending - Verster, Pieter (Verbum et ecclesia, 1996)
Salvation and welfare in the present time, covenant and mission In the theological debate on salvation and welfare an important question that must be asked is the one concerning the relevance of the present time and world. The Marxist view presents the radical revolution as solution. The neo-Marxist view is that the revolution should continue. The theology of hope regards future freedom as way of salvation. The theology of liberation regards the exodus of the poor as salvation. The theology of reconstruction looks forward to a future where justice and human rights will be stressed. Salvation and welfare in the present time should, however, be related to the covenant of God. This is also very important for the way in which salvation must be seen from a missiological point of view.